Transcriptional insight into the effect of benzalkonium chloride on resistance and virulence potential in Salmonella Typhimurium - Park, Sojung; Yoon, Hyunjin (Microbiological Research, 2023)
Benzalkonium chloride (BC), a class of quaternary ammonium compounds (QACs), is widely used as a surface disinfectant in food industries and hospitals. To date, little is known about the underlying mechanisms of how bacterial pathogens respond to and develop resistance against QACs. We investigated the genome-wide transcriptional responses of Salmonella enterica serovar Typhimurium to treatment with BC and identified the genetic determinants required for bacterial resistance to BC, including ramRA, phoU-pstBACS, cpxARP, and ugpQCEAB. Remarkably, RamA, a member of the AraC/XylS family transcription regulators, increased its transcription upon treatment with BC and its absence rendered Salmonella susceptible to BC treatment, indicating the positive role of RamA in BC tolerance. The attenuated BC resistance of the ΔramA mutant strain was complemented by the introduction of AcrA in trans, indicating that the AcrAB-TolC efflux system activated by RamA is required for the resistance of Salmonella to BC. Meanwhile, sublethal concentrations of BC downregulated the mRNA expression of genes associated with Salmonella pathogenicity island 1 (SPI-1) and SPI-2, which are critical determinants of Salmonella virulence. In accordance with the downregulation of SPI-1, HilD, the master regulator of SPI-1, also decreased upon treatment with BC; however, the absence of Lon protease nearly nullified the BC-mediated repression of SPI-1 genes. Intriguingly, overexpression of RamA repressed the transcription of SPI-1 genes; however, its negative regulation of SPI-1 expression is likely to be independent of the Lon-mediated regulation of SPI-1. These results demonstrated that treatment with sublethal concentrations of BC not only stimulates Salmonella to develop resistance mechanisms against BC, but also influences Salmonella virulence.
Keywords: Benzalkonium chloride; On-resistance; Quaternary ammonium compound; Resistance; Resistance potential; Salmonella pathogenicity islands; Salmonella typhimurium; Transcriptomes; Virulence; Virulence potential; Bacterial Proteins; Benzalkonium Compounds; Gene Expression Regulation, Bacterial; Salmonella typhimurium; Virulence; Benzalkonium chloride; Resistance; Salmonella Typhimurium; Transcriptome; Virulence